The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1073/pnas.1907354116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of orexin receptor antagonist and GABA A agonist on sleep and physical/cognitive functions after forced awakening

Abstract: The majority of patients with insomnia are treated with hypnotic agents. In the present study, we evaluated the side-effect profile of an orexin receptor antagonist and γ-aminobutyric acid A (GABAA) receptor agonist on physical/cognitive functions upon forced awakening. This double-blind, randomized, placebo-controlled, cross-over study was conducted on 30 healthy male subjects. Fifteen minutes before bedtime, the subjects took a pill of suvorexant (20 mg), brotizolam (0.25 mg), or placebo and were forced awak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
(58 reference statements)
1
22
0
Order By: Relevance
“…The relation between the actions of these neurosubstances and sleeping energy metabolism remains to be addressed in human studies. Of note, we observed that an orexin receptor antagonist induces sleep, modifies sleep architecture, and suppresses energy expenditure 27 .…”
Section: Sleep and Rqmentioning
confidence: 76%
See 1 more Smart Citation
“…The relation between the actions of these neurosubstances and sleeping energy metabolism remains to be addressed in human studies. Of note, we observed that an orexin receptor antagonist induces sleep, modifies sleep architecture, and suppresses energy expenditure 27 .…”
Section: Sleep and Rqmentioning
confidence: 76%
“…Sleep was recorded polysomnographically using a PSG-1100 system (Nihon Kohden). The records were scored every 30 s to stage wakefulness (W), stage 1, stage 2, slow wave sleep (SWS), and rapid eye movement (REM) sleep according to standard criteria 8,27 .…”
mentioning
confidence: 99%
“…Its clinical development encompasses the largest and longest studies conducted with a hypnotic ([55–59], reviewed in [28, 60]). Suvorexant is generally well‐tolerated and, like almorexant, does not impair cognition [61]. PSG analyses also indicate a dominant effect on REM sleep in comparison to non‐REM (NREM) [34].…”
Section: Drug Discovery and Developmentmentioning
confidence: 99%
“…Moreover, DORAs -different to benzodiazepines, Z-drugs, and sedating antidepressants -do not impair physical and cognitive functions after e.g. forced awakening from night-sleep [31,32]. Orexin receptor antagonists therefore will very likely be first-choice agents in the treatment of insomnia with a special emphasis on the prevention of neurodegenerative disorders.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%